2022
DOI: 10.1590/fst.103621
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable oils in emulsified meat products: a new strategy to replace animal fat

Abstract: The change in the lifestyle of modern consumers has increased the demand for meat products considered healthier, due tothe addition of animal fat in emulsified meat products, ingredient directly associated with the emergence of chronic diseases such as obesity and hypertension. In this sense, lipid reformulation processes aimed at replacing animal fat with other sources that are considered healthier, such as vegetable oils, appear as an innovative option for the production of meat products. However, it is nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 78 publications
0
8
0
2
Order By: Relevance
“…As indicated by recent studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], the addition of vegetable oils, including, for example, flaxseed oil, chia oil, hemp oil, canola oil, olive oil, sunflower oil, tiger nut oil, algae oil, or the use of vegetable oils as a substitute for animal fat in meat products meets the nutritional demand for enriching such products with unsaturated fatty acids (n-3, n-6, and n-9). Excessive consumption of animal products with large amounts of fat leads to obesity, and increases the risk of cardiovascular disease and the risk of developing certain cancers, such as of the colon [ 9 ]. In addition, consumers of meat preparations seek products containing natural ingredients, and insist that the use of synthetic additives be minimized or discontinued [ 2 ].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…As indicated by recent studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], the addition of vegetable oils, including, for example, flaxseed oil, chia oil, hemp oil, canola oil, olive oil, sunflower oil, tiger nut oil, algae oil, or the use of vegetable oils as a substitute for animal fat in meat products meets the nutritional demand for enriching such products with unsaturated fatty acids (n-3, n-6, and n-9). Excessive consumption of animal products with large amounts of fat leads to obesity, and increases the risk of cardiovascular disease and the risk of developing certain cancers, such as of the colon [ 9 ]. In addition, consumers of meat preparations seek products containing natural ingredients, and insist that the use of synthetic additives be minimized or discontinued [ 2 ].…”
Section: Introductionmentioning
confidence: 59%
“…According to Rodriguez-Estrada et al [ 49 ], vegetable fats can be lost or reacted during thermal processing. Reductions in the fat content of meat products using a substitute for animal fat, most commonly lard, with vegetable fats have been confirmed in a number of research papers [ 9 , 10 , 11 , 13 , 14 ]. In a study by Barros et al [ 11 ], a significant decrease in the fat content of hamburgers was observed with animal fat replacement in the form of tiger nut oil.…”
Section: Resultsmentioning
confidence: 99%
“…Perdas de peso por cozimento para sistemas de emulsão de carne com redução de gordura, são afetadas pelo tipo de óleo vegetal usado e tipo de cozimento proposto, e o uso de óleo vegetal aumentam estes valores (Choi et al, 2009). A aceitação deste produto pode ser limitada pelo consumidor, pois a inclusão de óleo vegetal precisa apresentar boas características nas propriedades tecnológicas com o menor impacto na aceitação global do produto (Ganesan et al, 2018;Lima et al, 2022). Porém, a principal vantagem da utilização de óleo vegetal em substituição àgordura animal em produtos cárneos é aumentar a razão entre ácidos graxos poliinsaturados e saturados, além de diminuir a razão entre ômega 6 e ômega 3, valores importantes para a saúde do consumidor.…”
Section: Discussionunclassified
“…Porém, a principal vantagem da utilização de óleo vegetal em substituição àgordura animal em produtos cárneos é aumentar a razão entre ácidos graxos poliinsaturados e saturados, além de diminuir a razão entre ômega 6 e ômega 3, valores importantes para a saúde do consumidor. (Lima et al, 2022) A composição química, em proteína e resíduo mineral fixo não apresentaram diferença estatística significativa. Nos estudos de Lacerda (2016), ao comparar a formulação controle com as formulações que continham substituições de gordura animal por óleo de canola em linguiça crua, não foi encontrado diferença entre os tratamentos para a composição química.…”
Section: Discussionunclassified
“…Notably, the seeds also contain a considerable quantity of oil (33-38%). Vegetable oils are important nutrients for humans (Lima et al, 2022). Muskmelon seeds contain a good amount of crude fat up to 30% (Amin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%